Relationship of Angiogenesis and Oral Squamous Cell Carcinoma - Marla, V.; Hegde, V.; Shrestha, A. (Kathmandu University Medical Journal, 2017)
Angiogenesis is an important aspect of a variety of physiological and pathological processes; and depends on the alteration of the balance between pro-angiogenic and anti-angiogenic factors. The role of angiogenesis in the progression and metastasis of neoplasm is a well established phenomenon. With regards to oral squamous cell carcinoma, it is a field of ongoing research and requires validation for it being used as a mode of anti-cancer therapy. This review focuses on the concept of angiogenesis, the factors associated with it, the relationship of angiogenesis with oral epithelial dysplasia and oral squamous cell carcinoma; the methods of studying angiogenesis and anti angiogenic therapy.